2006
DOI: 10.1037/0003-066x.61.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Minority students of color and the psychology graduate pipeline: Disquieting and encouraging trends, 1989-2003.

Abstract: Trends since 1989 in the minority graduate pipeline in psychology are examined, with special focus on trends in recent years. Encouraging trends generally outweigh troubling ones at lower levels of the pipeline. However, in recent years disquieting trends dominate at the higher pipeline levels. Promising trends include a rise in the percentage (to nearly 25%) of minority psychology students receiving the bachelor's degree and a rise to more than 20% receiving the master's degree. Troubling trends include the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 29 publications
(39 reference statements)
2
125
1
Order By: Relevance
“…The proportion of ethnic minority students in this sample (28.3%) was higher than estimates of the proportion of ethnic minority students entering doctoral psychology programs. Maton and colleagues (Maton, Kohout, Wicherski, Leary, & Vinokurov, 2006) calculated that only 20% of students who entered PsyD programs and 22.1% of students who entered PhD programs in 2003 were ethnic minorities. More than a quarter (n 5 131; 27%) of students in the current study identified as belonging to another underrepresented group (i.e., other than ethnicity/race).…”
Section: Participantsmentioning
confidence: 99%
“…The proportion of ethnic minority students in this sample (28.3%) was higher than estimates of the proportion of ethnic minority students entering doctoral psychology programs. Maton and colleagues (Maton, Kohout, Wicherski, Leary, & Vinokurov, 2006) calculated that only 20% of students who entered PsyD programs and 22.1% of students who entered PhD programs in 2003 were ethnic minorities. More than a quarter (n 5 131; 27%) of students in the current study identified as belonging to another underrepresented group (i.e., other than ethnicity/race).…”
Section: Participantsmentioning
confidence: 99%
“…SCRA may also further promote mentoring programs targeted at marginalized groups (perhaps taking place all year round, not just at Biennial Conferences). Such programs must be proactive and address various levels of training (Maton et al, 2006). Instead of waiting for members of marginalized groups to find the field, SCRA should seek out promising undergraduate and graduate students.…”
Section: Discussionmentioning
confidence: 99%
“…These trends are particularly encouraging as other fields of psychology struggle to recruit and retain ethnic minority members (Commission on Ethnic Minority Recruitment, Retention, and Training in Psychology [CEMRRAT], 1997;Pickeren, 2004). In an article published in the American Psychologist, Ken Maton and his colleagues reported that ethnic minorities are less likely than non-minorities to enter or finish a doctoral program in psychology (Maton, Kohout, Wicherski, Leary, & Vinokurov, 2006). In addition, it seems that ethnic minorities face additional barriers in attaining positions of prestige in psychology.…”
Section: Inclusion Of Marginalized Groupsmentioning
confidence: 91%
See 1 more Smart Citation
“…The primary thrust of such research has been due to a critical awareness that disparities in educational outcomes between Whites and racially/ ethnically diverse groups continue to plague the U.S. (Niemann and Maruyama 2005). Additionally, having racially diverse student bodies in mental health training programs is critically important because of the need to serve effectively an increasingly multicultural, and internationally-born, client base in the U.S. (Maton et al 2006).…”
mentioning
confidence: 98%